Perencanaan Dan Perancangan Beach Club Di Pemuteran Beach, Gerokgak, Kabupaten Buleleng - I Gede Komang Wahyu Ari Trisna; I Nyoman Warnata; I Nyoman Gede Maha Putra (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2021)
Beach Club is an association of several activities located on the beach and provides recreational and relaxation facilities such as restaurants, rooftops, bars, lounges, sunbathing areas, swimming pools, and several other supporting facilities. Beach Club is very much needed apart from being a place of recreation as well as a place to relax, it can also support the needs of tourists who after carrying out activities around Pemuteran Beach because of the very attractive tourism potential with stunning natural beauty and the existence of marine tourism that can be enjoyed by tourists. Therefore Pemuteran Beach is one of the beaches visited by many tourists in the North Bali area. Then the basic concept that will be applied later is "Jus For Fun" which means just for fun. The design theme that will be used in planning and designing this Beach Club is "Tropical Architecture" which can adapt to buildings, climatic conditions in a tropical area (Pemuteran Beach).